The Prototype Electric Steering Gear Based Microcontroller Arduino - Narto, Amad; Suharto, Suharto; Catur, Regga Diko (RSF Conference Series: Engineering and Technology, 2023)
Globalization has led to the advancement of science and technology in all aspects of human life. The rapid development of science and technology significantly influences both learning methods and employment. As a result, many effective learning methods are being utilized, and one of them is the control system in electric steering gear, which enables the remote control of auxiliary machinery. Therefore, the creation of a demonstration tool for auxiliary machinery on ships is highly suitable for the era of globalization. The type of demonstrative tool created by the author is an updated version of the electric steering gear with remote control capabilities. The Research and Development method is employed in this study, which involves a process or steps to develop a new product or improve existing ones, including both hardware and software components. The model used in this development research is the procedural model, outlining the sequential and gradual steps from the initial process to the final one. The construction of the demonstrative tool for the updated electric steering gear involves three electronic modules: the ESP 8266 module, the Servo Motor, and the Wi-Fi module. The ESP functions as the microcontroller, the Servo Motor is responsible for the steering direction and angle position control, while Wi-Fi serves as the control medium. The author has made improvements to the electric steering gear demonstrative tool, which typically uses a lever, by implementing smartphone control as a substitute. The working system of this demonstrative tool is to set the degree of the steering angle position and respond to control signals by moving the shaft to the desired position. This system functions with the support of the automation control system provided by the electronic modules.